Standardized genetic diversity‐life history correlates for improved genetic resource management of Neotropical trees. Issue 6 (7th February 2018) - Lowe, Andrew J.; Breed, Martin F.; Caron, Henri; Colpaert, Nathalie; Dick, Christopher; Finegan, Bryan; Gardner, Mike; Gheysen, Godelieve; Gribel, Rogério; Harris, J. Berton C.; Kremer, Antoine; Lemes, Maristerra R.; et al.
Abstract: Aim: Life history traits and range size are key correlates of genetic diversity in trees. We used a standardized sampling protocol to explore how life history traits and range size relate to the magnitude, variance and structuring (both between‐ and within‐population) of genetic diversity in Neotropical tree species. Location: The Neotropics Methods: We present a meta‐analysis of new population genetic data generated for 23 Neotropical tree species (=2, 966 trees, 86 populations) across a shared and broad geographic area. We compared established population genetic metrics across these species (e.g., genetic diversity, population structure, fine‐scale genetic structure), plus we estimated the rarely used variance in genetic diversity among populations. We used a multivariate, maximum likelihood, multimodel inference approach to explore the relative influence of life history traits and range size on patterns of neutral genetic diversity. Results: We found that pioneer and narrow range species had lower levels but greater variance in genetic diversity—signs of founder effects and stronger genetic drift. Animal‐dispersed species had lower population differentiation, indicating extensive gene flow. Abiotically dispersed and pioneer species had stronger fine‐scale genetic structure, suggesting restricted seed dispersal and family cohort establishment. Main conclusions: Our multivariable and multispecies approach allows ecologically relevant conclusions, since knowing whether one parameter has an effect, or one species shows a response in isolation, is dependent on the combination of traits expressed by a species. Our study demonstrates the influence of ecological processes on the distribution of genetic variation in tropical trees, and will help guide genetic resource management, and contribute to predicting the impacts of land use change.